Risk analysis as a factor in the stability of the organization (Journal of Economic Research & Business Administration, 2016)
Any kind of business is related to different types of risk. If you look to the economic side, the risk - the probability of loss. Therefore, in everyday life the risk associated with the events that lead to the moral and material costs.The risk of shows any adverse condition. The concept of risk also means as the probability of loss is one of the resources of the company, in the process of income generation activities is incomplete or the ap-pearance of additional costs. The business risk in decision-making, not only determines the level of probability of loss and the probability of not exceeding those levels.
Keywords: stability; risk; analysis; financial condition; financial stability.